Build, borrow, or buy : solving the growth dilemma - Capron, Laurence; Mitchell, Will. (Boston, Mass. : Harvard Business Review Press, 2012)
How should you grow your organization? It is one of the most challenging questions an executive team faces and the wrong answer can break your firm. The problem is most firms' growth strategies emphasize just one type of growth but firms falling into this implementation trap usually end up losing out to a competitor whose approach is more inclusive. Drawing on decades of research and teaching, the authors find that a firm's aptitude for determining the best resource pathways for growth has a defining impact on its success. They have come up with a helpful framework, reflecting practices of a variety of successful global organizations, to determine which path is best for yours. Written for large multinationals and emerging firms alike, this book will help solve a perennial question and will guide you through change while priming your organization for optimal growth.
Introduction: two funerals and a wedding -- The resource pathways framework -- When to build : internal development versus external sourcing -- When to borrow via contract : basic contract versus alliance -- When to borrow via alliance : alliance versus acquisition -- When to buy : acquisition versus the alternatives -- Realigning your resource portfolio -- Developing your enterprise selection capability -- Appendix A: The resource pathways framework -- Appendix B: The author's research program.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Business enterprises -- Finance; Strategic planning; Decision making; Success in business; Business enterprises -- Finance; Decision making; Strategic planning; Success in business; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books